Enhanced hate speech detection in social media using transformer-based models - Tabasshum, Anika; Ashrafi, Fairuz Tasnim; Afreen, Sadia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.